Translocation t(1;11)(p32;q23) with MLL-EPS15 fusion gene formation in acute leukemias: a review and 6 new case reports. Approaches to minimal residual disease monitoring - G. A. Tsaur; A. M. Popov; O. M. Plekhanova; A. M. Kustanovich; O. V. Aleynikova; T. L. Gindina; A. S. Demina; A. Ye. Druy; S. Yu. Kovalev; K. L. Kondratchik; A. V. Misyurin; N. V. Myakova; et al. (Онкогематология, 2014)
We performed clinical and laboratory characterization of patients with rare translocation t(1;11)(p32;q23) leading to MLL-EPS15 fusion gene formation. Study cohort consisted of 33 primary acute leukemia (AL) cases including 6 newly diagnosed and 27 patients previously described in literature. Among study group patients t(1;11)(p32;q23) was found most frequently in infant AL cases (median age 8 months). In acute lymphoblastic leukemia (ALL) male/female ratio was 1:3, in acute myeloid leukemia (AML) it was 1:1. Additional cytogenetic aberrations in 38 % of patients were revealed. The most frequent breakpoint position in EPS15 gene was intron 1. Four different types of MLLEPS15 fusion gene transcripts were detected. Primers-probe-plasmid combination for MLL-EPS15 fusion gene transcript monitoring by realtime quantitative polymerase chain reaction (RQ-PCR) was developed and successfully applied. In 3 patients RQ-PCR was done on genomic DNA for absolute quantification of MLL-EPS15 fusion gene. High qualitative concordance rate (92 %) was noted between minimal residual disease data obtained in cDNA and genomic DNA for MLL-EPS15 fusion detection.